International migration outlook (Paris, 2013)
"This publication analyses recent development in migration movements and policies in OECD countries and some non member countries including migration of highly qualified and low qualified workers, temporary and permanent, as well as students. This edition also contains two special chapters on topical issues: fiscal impact of migration and discrimination."